Factors Associated With Attrition in a 10‐year Longitudinal Study of Young People: Implications for Studies of Employment in School Leavers. (16th June 2016) - Delfabbro, Paul; Winefield, Helen; Winefield, Anthony; Malvaso, Catia; Plueckhahn, Tanya
Abstract : Objectives: The aim of this methodological evaluation study is to examine the likely effects of sample attrition on the social and psychological outcomes variables often examined in studies of school leavers and which have been included in many studies of employment. Methods: We examine the effects of sample attrition based on analysis of a recently completed 10‐year longitudinal study of school leavers. Results: The results showed that the dropouts differed from the stayers on a number of variables. For example, the dropouts tended to be older and were more likely to use illicit substances, such as marijuana. Males were more likely to drop out than females. On the other hand, the dropouts did not differ from the stayers in terms of the main variables of interest: psychological well‐being (including self‐esteem, suicidal ideation, life satisfaction, and other related variables). Conclusions: Given that longitudinal studies of adolescents are often used to inform theoretical developments and policies relating to early intervention and longer term outcomes, these findings provide cautious optimism that selective attrition does not pose a major threat to the external or internality validity of employment studies investigating psychological or social outcomes, but it does raise questions about the importance of dealing with missing data in studies of high‐risk behaviours.